PERAN KEPEMIMPINAN RELIGIUS DALAM MEMBANGUN BUDAYA ORGANISASI PENDIDIKAN YANG HUMANIS DAN ETIS - wahyu hidayat; Junaidah; Muhammad Suhardi (Al-Mahabbah : Jurnal Manajemen Pendidikan Islam, 2025)
Religious leadership in Islamic educational institutions plays a strategic role in shaping a humanistic and ethical organizational culture. Amid growing moral challenges and value crises in education, there is a pressing need for leadership that is not only managerial but also deeply rooted in spiritual values. This study aims to analyze the role of religious leadership in developing an organizational culture that emphasizes human dignity and strengthens ethical values in educational governance. Using a literature review approach, this article examines recent studies related to religious leadership, organizational culture, and Islamic educational ethics. The findings reveal that the core characteristics of religious leaders include integrity, exemplary conduct, and strong adherence to Islamic teachings, which are reflected in their daily behavior and institutional policies. The organizational culture fostered by such leadership tends to be inclusive, participatory, and anchored in values such as rahmah (compassion), justice, and trustworthiness. Moreover, ethical values are not merely formal norms but are internalized within the collective behavior of school communities. The study concludes that religious leadership serves as a foundational pillar in creating a sustainable and dignified Islamic education ecosystem. These findings are expected to contribute to the development of Islamic leadership models that are relevant to contemporary educational management needs.